The Effect of Leverage, Profitability, Liquidity, Firm Size, and RETA on Dividend Policy - Adang, Ferry; Wijoyo, Amin; Goodwin, Bryan; Wiryajaya, Steven (Sean Institute, 2025)
The study aims to obtain empirical evidence regarding the influence of leverage, profitability, liquidity, firm size, and RETA as independent variables on dividend policy as the dependent variable. The population used in this study consists of energy sector companies listed on the Indonesia Stock Exchange during the years 2021–2023. The sample consists of 51 companies, comprising 17 companies over a three-year study period. The model used in this study is Microsoft Excel software, processed using the E-views 10 program.